2011
DOI: 10.1007/s11269-011-9846-6
|View full text |Cite
|
Sign up to set email alerts
|

A GIS Framework for Changing Cropping Pattern Under Different Climate Conditions and Irrigation Availability Scenarios

Abstract: Irrigation water availability is a main driver which determines cropping patterns for an irrigation area. Irrigation water availability will potentially reduce due to changes in climate and irrigation extraction limits. Cropping patterns should be adjusted to meet this challenge. This study presents a new approach for assessing future cropping patterns using GIS in combination with an Irrigation Water Availability Simulation model (IWAS) at irrigation area scale. The IWAS-GIS framework was developed for analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Former studies have shown that the increase in crop water productivity will counteract the increase in the water demand from crops due to the rising of temperatures (Sun et al, ; Turral et al, ). Potential means by which agriculture can cope with water scarcity and climate change are by changing cropping patterns based on available water resources, such as cutting down the area of water‐intensive crops (crop with low water productivity) or adjusting to the crops with higher water productivity (Sun et al, ; Wang, Chen, & Peng, ). Abdi‐Dehkordi, Bozorg‐Haddad, and Loaiciga () showed that although climate change will increase the water demand of crops, the proper management and modification of cropping patterns will benefit agricultural incomes while reducing the water requirement of crops on a regional scale, and the results indicated that under baseline climate and climate change scenarios, the optimum cropping pattern will increase agricultural incomes by 14% and 17%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Former studies have shown that the increase in crop water productivity will counteract the increase in the water demand from crops due to the rising of temperatures (Sun et al, ; Turral et al, ). Potential means by which agriculture can cope with water scarcity and climate change are by changing cropping patterns based on available water resources, such as cutting down the area of water‐intensive crops (crop with low water productivity) or adjusting to the crops with higher water productivity (Sun et al, ; Wang, Chen, & Peng, ). Abdi‐Dehkordi, Bozorg‐Haddad, and Loaiciga () showed that although climate change will increase the water demand of crops, the proper management and modification of cropping patterns will benefit agricultural incomes while reducing the water requirement of crops on a regional scale, and the results indicated that under baseline climate and climate change scenarios, the optimum cropping pattern will increase agricultural incomes by 14% and 17%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The data comprising all of these elements can be broken down into nested spatial layers in a GIS system, each with a geographic coordinate derived from GPS data that roots it in the local geography [13]. Then, these spatial layers can be processed and analysed in a GIS system in a variety of ways to forecast agricultural trends, expose crop and soil conditions and spatial interconnections, monitor pests, track changes in land use, and aid in the conservation of biodiversity [14][15][16][17]. They can be used to map agricultural production barriers and identify their spatial locations, as well as to uncover new data that could enhance agricultural sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…In the face of future water scarcity, possible means for the agricultural sector to adapt are via changes in cropping patterns and adjustments according to available water resources (Boustani & Mohammadi 2010). Adjustment of cropping patterns according to irrigation water availability, such as reducing the area of water-intensive crops or changing crop types to ones with more efficient water use, provides a potential means of alleviating irrigation water scarcity (Wang et al 2011).…”
Section: Introductionmentioning
confidence: 99%